Probing Solid-State Interface Kinetics via Alternating Current Electrophoretic Deposition: LiFePO4 Li-Metal Batteries - Su Jeong Lee; Byoungnam Park (Applied Sciences, 2025)
This work presents a comprehensive investigation into the interfacial charge storage mechanisms and lithium-ion transport behavior of Li-metal all-solid-state batteries (ASSBs) employing LiFePO4 (LFP) cathodes fabricated via alternating current electrophoretic deposition (AC-EPD) and Li1.3Al0.3Ti1.7(PO4)3 (LATP) as the solid-state electrolyte. We demonstrate that optimal sintering improves the LATP–LFP interfacial contact, leading to higher lithium diffusivity (~10−9 cm2∙s−1) and diffusion-controlled kinetics (b ≈ 0.5), which directly translate to better rate capability. Structural and electrochemical analyses—including X-ray diffraction, scanning electron microscopy, cyclic voltammetry, and rate capability tests—demonstrate that the cell with LATP sintered at 900 °C delivers the highest Li-ion diffusivity (~10−9 cm2∙s−1), near-ideal diffusion-controlled behavior (b-values ~0.5), and superior rate capability. In contrast, excessive sintering at 1000 °C led to reduced diffusivity (~10−10 cm2∙s−1). The liquid electrolyte system showed higher b-values (~0.58), indicating the inclusion of surface capacitive behavior. The correlation between b-values, diffusivity, and morphology underscores the critical role of interface engineering and electrolyte processing in determining the performance of solid-state batteries. This study establishes AC-EPD as a viable and scalable method for fabricating additive-free LFP cathodes and offers new insights into the structure–property relationships governing the interfacial transport in ASSBs.